GLOBALIZATION’S INFLUENCE ON THE COMPETITIVENESS OF NATIONAL ECONOMY - Aničić, Dušan; Nestorović, Olgica (Journal of process management and new technologies, 2019)
The process of globalization is the characteristics of modern trends in world economy, implying open national borders for uninterrupted movements of products, capital and labor force around the world. Although the process of globalization caused huge economic growth and technology advance, numerous faults and contradictions of the process have become obvious in the recent decades. Nowadays, the role of globalization is considered overrated, the reality being very different from the promises, and therefore the trust into the process has vanished, as well as elites and institutions that advocated and imposed it. National economies, especially in transition countries, strive to catch up with the developed countries and take desired positions in the global market through the increase in their competitiveness.